PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT MATAHARI DUTA PLAZA DENPASAR - Ni Putu Rika Juliantari; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Business competition is getting tougher every day, this is very much felt in the retail sector business. This is indicated by the increasing number of competitors that have emerged and also a decrease in the percentage of company sales, as well as the emergence of other problems, especially in the human resource factor. This study aims to determine and analyze empirically the effect of emotional intelligence and work stress on employee productivity at PT. Matahari Duta Plaza Denpasar.This study uses quantitative and qualitative data, and uses primary and secondary data sources. Determination of the sample using stratified random sampling technique of 62 employees as respondents and data collection methods using a questionnaire. The method of analysis uses multiple linear regression analysis and tested using the IBM SPSS Statistic 20 software. Based on the test results, it is stated that emotional intelligence has a positive and significant effect on employee productivity at PT Matahari Duta Plaza Denpasar, while job stress has a negative and significant effect on employee productivity at PT Matahari Duta Plaza Denpasar.